N deposition may accelerate grassland degradation succession from grasses- and sedges-dominated into forbs-dominated in overgrazed alpine grassland systems on Qinghai-Tibetan Plateau - Hao Shen (Elsevier, 2021)
Alpine grasslands are sensitive to grazing and atmospheric nitrogen (N) deposition. Despite increases in N deposition, few field studies have assessed the effects of grazing in conjunction with increased N deposition on alpine grassland vegetation.In this two-year field study, we examined the effects of overgrazing and overgrazing plus N deposition on eco-physiological processes of alpine grassland plants at the functional group level. We found that both overgrazing and overgrazing plus N deposition altered species composition and the dominance of three plant functional groups (grasses, sedges, and forbs) in an alpine meadow and alpine steppe.In the overgrazing and overgrazing plus N deposition treatments, forbs dominated the plant community. Grass and sedge dominance decreased substantially, relative to a ungrazed treatment. The underlying eco-physiological processes that led to the forb-dominated plant community differed between the overgrazing and overgrazing plus N deposition treatments. Overgrazing plus N deposition increased forb dominance both directly by selective herbivory and indirectly by enhancing forb photosynthetic rates.Our results suggest that overgrazing concomitant with increases in N deposition will likely shift the plant community composition of alpine grasslands on the Qinghai-Tibetan Plateau from grass/sedge communities to forb-dominated communities in the future.